ответ:
(24+х)-21=10. (24+х)-21=10
24+х=21+10. 24-21+х=10
24+х=31. 3+х=10
х=31-24. х=10-3
х=7. х=7
(24+7)-21=10. (24+7)-21=10
10=10. 10=10
(45-у)+18=58. (45-у)+18=58
45-у=58-18. 45+18-у=58
45-у=40. 53-у=58
у=45-40. у=58-53
у=5. у=5
(45-5)+18=58. (45-5)+18=58
58=58. 58=58
56-(х+12)=24. 56-(х+12)=24
х+12=56-24. 56-12+х=24
х+12=32. 44+х=24
х=32-12. х=44-24
х =20. х=20
56-(20+12)=24. 56-(20+12)=24
24=24. 24=24
55-(х-15)=30. 55-(х-15)=30
х-15=55-30. 55+15-х=30
х-15=25 70-х=30
х=25+15. х=70-30
х=40. х=40
55-(40-15)=30. 55-(40-15)=30
30=30. 30=30
пошаговое объяснение:
a) √2cos2x< < 1 b)2㏒²₅x-10㏒₂₅x+2=0
cos2x< < 1/√2=√2/2 2log²₅x-10log₅^²x+2=0
2x=π/4+2πk, k∈z 2log²₅x-10/2log₅x+2=0
x=π/8+πk, k∈z пусть log₅x=t
2t²-5t+2=0
d=(-5)²-4*2*2=25-16=9
x₁=(5+3)/2*2=8/4=2
x₂=(5-3)/2*2=2/4=1/2=0.5
решил как уравнение.